Comparison of serum levels of vitamin D in Graves’ patients and healthy individuals - Valizadeh, Neda; Fakhraei, Roya; Mehdizadeh, Alireza (Medicinski časopis, 2018)
Objective: Relationship between Graves’ disease and vitamin D deficiency is a challenging matter and some of researchers had been suggested the role of vitamin D deficiency in the pathogenesis of Graves’ disease. We designed this study to evaluate serum level of vitamin D in Graves’ disease.Methods: During a cross-sectional study in 2014, 27 patients with Graves’ disease and 29 healthy subjects were enrolled. From all of patients and healthy group intravenous blood samples for assessment of serum vitamin D levels were taken. Serum level of vitamin D of all of patients and healthy group compared with each other.Results: The mean of age in Graves’ patients and healthy group were 41.23 ± 2.58 and 34.40 ±1.44 years respectively (P=0/02) and there was significant difference between age in two groups. 77.8 and 58.6% of Graves’ patients and healthy groups were female respectively (P=0/12).Serum level of vitamin D in Graves’ patient was 18.04± 1.92 ng/ml and in healthy controls was 17.15±2.06 ng/ml and there is not statistically significant difference in vitamin D levels between two groups (p=0.75). Vitamin D status did not differ between two groups of study (p-value=0.92).Conclusion:  According to our study, there is no association between serum vitamin D levels and Graves' disease.